The study and analysis on the significant relationship between economic variable (GDP, CPI & IR) and corporate earning performance (EPS) on finance sector listed on KLSE main board from 1995 – 2001 / Sharifah Roziah Wan Bujang - Wan Bujang, Sharifah Roziah (2003)
Investors either individual or institutional are concerned very much with the corporate earning performance for investment decision. This is especially true for those who invest based on fundamental analysis technique. Corporate earning performance is one of the basis information or data that will be analyse when doing fundamental analysis of a company.